The antimicrobial study of white turmeric (Curcuma zedoaria) extracted using deep euthectic solvent (DES) and ultrasonication - Timotius Agung Soripada; Erny Tandanu; Refi Ikhtiari (Jurnal Pendidikan Kimia (JPKIM), 2023)
This research is prompted by the emergence of various cases of infectious diseases and antibiotic resistance that often occur and the development of the latest research methods in the field of medicinal plants. One of the medicinal plants that is often used is Curcuma zedoaria which is generally extracted using conventional solvents. This research aims to find new innovations in the extraction process of medicinal plants. This research is a laboratory experiment carried out in vitro. This research uses the latest solvent, called DES (Deep Eutectic Solvent) with the help of ultrasonication to extract active compounds from C. zedoaria as a natural anti-bacterial. DES is known as an environmentally friendly solvent, cheap, easy to make, and is still relatively new in Indonesia. The C. zedoaria extraction process uses two types of DES solvent composition assisted by a ultrasonicator. The research results show that: White turmeric extract (C. zedoaria) obtained by extraction using DES solvent and ultrasonication.  Ultrasonication results using 30%, 70% and 100% DES solvent showed antimicrobial properties against Escherichia coli with a lower zone of inhibition compared to the antibiotic ciprofloxacin. Ultrasonication results using 30%, 70% and 100% DES solvent showed antimicrobial properties against Staphylococcus aureus with a lower zone of inhibition compared to ciprofloxacin. TLC data shows that the white turmeric extract obtanined contains various antimicrobial substances which allows to inhibit each other to such an extent that their activity is lower than ciprofloxacin.Keywords: C. zedoaria; Deep eutectic solvent; Escherichia coli; Staphylococcus aureus; Ultrasonication